PENYADARAN DIRI DALAM UPAYA PEMBENTUKAN KARAKTER SANTRI RAYON K. H. AHMAD BASYIR AS PP. ANNUQAYAH LATEE - Muhammad Nihwan; Moh Mansur; Mukhlis Mukhlis; Bambang Hendriyanto (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2022)
Pesantren which generally focuses in good attitude and develops insight is hoped being a place of building santris self. By the unique sign, in globalization era, Pesantren is right place to build the character of Islamic generation. This research has goal to know self-awareness and the steps applying in building santris character of Rayon K. H. Ahmad Basyir AS. Research method used is field study research with qualitative approaching. The research result is that building santris character of Rayon K. H. Ahmad Basyir AS is to apply concrete steps in order to grow self-awareness, such as persuasive approaching to santri who has problem, and make programs that supports the thing to grow self-confidence, self-responsibility, and honesty.